شیکردنەوەى جوگرافی بۆ سەرپەڕیی پلەى گەرمى و شەپۆلە گەرم و ساردەکان لە پارێزگاى سلێمانى بە پشت بەستن بە میتۆدى (ETCCDI) - أحمد, پ.د سۆران حمە أمین; علي, پ.ی.د پێشەوا محمد; أحمد, خوێندکارى دکتۆرا م.چیمەن عبدالله (Sulaimani Journal for Humanities, 2023)
This study is about extreme temperature, it is based on the method (ETCCDI) using the advanced software (R-4.2.0), by taking time series daily data for (7) weather stations (Dukan, Chawarta, Penjwen, Sulaimani, Bazian, Chamchamal, Darbandikhan) after their quality control, to determine the value of both the maximum and the minimum temperatures and hot and cold waves, which varies among the stations, because of the location of the stations and natural structures are different in altitude and both land and water areas. However, this value varies from month to month and from year to year, and at the same station, due to the influence of unstable climatic factors. The results showed that during the study period, the lowest temperature (TN10p), cold waves, FD, and ID decreased, while both the hot days (TX90p) and hot waves increased. It was at the lowest temperature compared to the highest one in the study area during the study period; therefore, the phenomenon of freezing was reduced. This study has provided information that is useful to the public, policymakers, system planners, and resource managers.
Keywords: Keywords Extreme temperature; (ETCCDI); heat waves; cold waves